Seismic fracture analysis of concrete gravity dams including dam-reservoir interaction - Calayir, Y; Karaton, M (Pergamon-Elsevier Science Ltd, 2005)
In this study, the seismic fracture response of concrete gravity dams is investigated with considering the effects of dam-reservoir interaction. A co-axial rotating crack model (CRCM), which includes the strain softening behavior, is selected for concrete material. The dynamic equilibrium equations of motion for the dam-reservoir system are solved by using the improved form of the HHT-alpha time integration algorithm. Two-dimensional seismic analyses of Koyna gravity dam are performed by using the 1967 Koyna earthquake records for numerical application. The effects of cracking on the seismic response of concrete gravity dams are discussed. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: seismic fracture; concrete gravity dam; dam-reservoir interaction; non-linear analysis